2012
DOI: 10.1007/s11357-012-9463-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of epigenetics in human aging and longevity: genome-wide DNA methylation profile in centenarians and centenarians’ offspring

Abstract: The role of epigenetics in the modulation of longevity has not been studied in humans. To this aim, (1) we evaluated the DNA methylation from peripheral leukocytes of 21 female centenarians, their 21 female offspring, 21 offspring of both non-long-lived parents, and 21 young women through ELISA assay, pyrosequencing analysis of Alu sequences, and quantification of methylation in CpG repeats outside CpG AGE (2013) 35:1961-1973 DOI 10.1007 islands; (2) we compared the DNA methylation profiles of these populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
123
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(128 citation statements)
references
References 34 publications
3
123
1
1
Order By: Relevance
“…They differ in two major ways: (i) the rate of change is much higher in early life than later life, and (ii) the genomic locations of the changes are quite different. In early life, DNA methylation is gained globally, but more at island shores and intergenic regions, while in later life, DNA methylation is lost globally, but still gained at islands and shores (Alisch et al ., 2012; Gentilini et al ., 2013; McClay et al ., 2014). …”
Section: Dna Methylation Dynamics During Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…They differ in two major ways: (i) the rate of change is much higher in early life than later life, and (ii) the genomic locations of the changes are quite different. In early life, DNA methylation is gained globally, but more at island shores and intergenic regions, while in later life, DNA methylation is lost globally, but still gained at islands and shores (Alisch et al ., 2012; Gentilini et al ., 2013; McClay et al ., 2014). …”
Section: Dna Methylation Dynamics During Agingmentioning
confidence: 99%
“…However, some individuals would likely be in the ‘off‐diagonal’ region of this comparison, with an epigenetic age that is higher (‘epigenetically old’) or lower (‘epigenetically young’) than their chronological age. This trend has already been observed using the age predictors described in many of the studies described in Table 1, one study in particular found that centenarians had an unusually young epigenetic age (Gentilini et al ., 2013). An intriguing possibility is to predict health outcomes for those in the epigenetically old or epigenetically young groups relative to those who display concordant epigenetic and chronological ages, supported by a very recent study which associated accelerated epigenetic age with increased mortality (Marioni et al ., 2015) (Fig.…”
Section: What Can We Learn From Dna Methylation and Aging?mentioning
confidence: 99%
“…In the human aging process, alterations of DNA methylation indicate a loss of epigenetic control and relate to pathological phenotypes [2,3]. Today, epigenome-wide association studies (EWAS) have established general knowledge on age-related methylation patterns in humans [4-8].…”
Section: Introductionmentioning
confidence: 99%
“…However, such human longevity-associated genes (LAGs) seem to be very rare, and although a few have been confirmed in independent studies (2,3), their existence remains controversial. More recently, epigenetic changes associated with human longevity have also been documented (7).…”
mentioning
confidence: 99%